2021
DOI: 10.1007/s11664-020-08729-z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of CeO2/CoWO4 Hybrid Nanocomposites for High Photocatalytic Performance and Investigation of Antimicrobial Activity

Abstract: In this work, novel CeO 2 /CoWO 4 heterostructured nanocomposites (NCs) were synthesized via a hydrothermal method. X-ray diffraction, high-resolution transmission electron microscopy, UV-Vis diffuse reflectance spectroscopy and photoluminescence spectroscopy were carried out to determine the crystal structure, deep morphology, optical properties, and charge separation of the obtained photocatalysts (PCs), respectively. In comparison to the pristine CoWO 4 , the CeO 2 and CeO 2 /CoWO 4 PCs demonstrated enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…These hot electrons were crucial in improving the catalytic activity of the nanoparticles, outpacing other metal-decorating techniques. The results of this investigation showed that, when added to the NiO surface, Fe-doped NiO nanoparticles produced catalytic activity that was more efficient overall than metal decorations and noble metal decorations [75][76][77][78][79][80][81][82]. The results demonstrate the enhanced photocatalytic capabilities of Fe-doped NiO nanoparticles for the degradation of Rh-B dye in visible light.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…These hot electrons were crucial in improving the catalytic activity of the nanoparticles, outpacing other metal-decorating techniques. The results of this investigation showed that, when added to the NiO surface, Fe-doped NiO nanoparticles produced catalytic activity that was more efficient overall than metal decorations and noble metal decorations [75][76][77][78][79][80][81][82]. The results demonstrate the enhanced photocatalytic capabilities of Fe-doped NiO nanoparticles for the degradation of Rh-B dye in visible light.…”
mentioning
confidence: 71%
“…Metals were strategically added to metal-oxide nanoparticles in order to efficiently overcome the limitations of the photocatalytic activity of the metal-oxide nanoparticles. Metal doping or the decorating of metal-oxide nanoparticles resulted in a decrease in the bandgap energy and particle size, improving the nanoparticles' ability to absorb light in the visible spectrum [75][76][77][78]. The effectiveness of the targeted dye molecules' breakdown was subsequently improved by this change.…”
mentioning
confidence: 99%
“…Due to better awareness of environmental challenges among governments, businesses, and scholars, investigations on green synthesis and environmental remediation have expanded significantly . Semiconductor-based photocatalytic technologies are considered some of the most promising approaches for addressing environmental degradation and the energy crisis due to their capacity to efficiently gather renewable solar energy. , However, the bulk of semiconductor photocatalysts identified so far function moderately in the visible range. , The photocatalytic activity of such materials is improved in this context by optimizing metal grafting/doping , and connecting one semiconductor material with other materials to generate heterojunction . It has been shown that creating a heterojunction between two semiconductors is a successful method for forming improved photocatalysts .…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 However, the bulk of semiconductor photocatalysts identified so far function moderately in the visible range. 4 , 5 The photocatalytic activity of such materials is improved in this context by optimizing metal grafting/doping 6 , 7 and connecting one semiconductor material with other materials to generate heterojunction. 8 It has been shown that creating a heterojunction between two semiconductors is a successful method for forming improved photocatalysts.…”
Section: Introductionmentioning
confidence: 99%